Eksistensi Perempuan Dalam Novel Karsa Karya Elizabeth Alicia: Kritik Sastra Feminisme - Purnama Hasibuan; Ikhwanuddin Nasution; Nurhayati Harahap (Bahasa Indonesia Prima, 2024)
Literature plays an important role in everyday life because it can help us understand the world through stories, poetry, and drama. Many literary works also contain human life, one of which is the existence of women. The existence of women means the existence of women who dare to refuse to be objects of men and fight for their rights. This research aims to describe the existence of intellectual women, women who can achieve socialist transformation of society, and women who refuse to be others in the novel Karsa by Elizabeth Alicia, a feminist literary criticism study based on Simone de Beauvoir's theory of existentialist feminism. The data source in this research uses the novel Karsa by Elizabeth Alicia, published by Median Books in 2023. This research uses a qualitative descriptive method. The data is presented in the form of quotations, narratives, and dialog between characters that contain women's existence. The data collection technique used in this research is data analysis, which identifies, classifies, describes, and draws conclusions. Then, the data found is analyzed using Simone de Beauvoir's theory of existentialism feminism. The results of the research can conclude that the existence of women in the novel Karsa by Elizabeth Alicia includes (1) intellectual women, (2) Women achieving societal transformation, and (3) Women rejecting their innocence.